(NpU[KIN I ~AJKOWSKIJs (NMONOGRAFIQs - (Ne(B. (NbERLQND (B-(N~ERNAQ(B.s ((NmOSKWAs (NmUZGIZAs, 1950)
(NiMQ pU[KINA NAWSEGDA WO[LO W ISTORI@ RUSSKOGO MUZYKALXNOGO TWOR^ESTWA(B.s
Keywords: (NMONOGRAFIQs